Parameter driven monitoring for a flip-chip LED module under power cycling condition. (March 2018) - Magnien, J.; Mitterhuber, L.; Rosc, J.; Schrank, F.; Hörth, S.; Hutter, M.; Defregger, S.; Kraker, E.
Abstract: In this paper, a parameter driven monitoring model is introduced, in which a flip-chip LED module was investigated during a power cycling test. This approach was investigated to develop a monitoring model to describe thermally induced solder fatigue as root cause of flip-chip failure in a power cycling test. As monitoring parameter the thermal resistance of the LED module was used, which was determined by thermal impedance measurements of the whole LED module, as well as for each LED chip itself. Further analyses of the occurring temperature at the LED junction recorded of each chip during the power cycling test were used to generate a prediction model. The evaluation of the temperature change allowed to forecast the number of cycles until failure. Highlights: Parametric monitoring model based on Rth to define remaining power-cycles until chip failure. Reliability model for flip-chip LEDs under power cycling conditions. Thermal impedance analysis as online monitoring tool for solder fatigue and lifetime prediction. Investigation of power cycling induced changes in LED module's region.